Magia e Superstição no Mediterrâneo Antigo - do Céu Fialho, Maria; Regina Candido, Maria; Simões Rodrigues, Nuno (Coimbra University Press, 2025)
This volume allowed us to gather Brazilian, Spanish, French, Greeks, Italians. and Portuguese specialists who search about magic and superstition in the Ancient Mediterranean. The theme circled around the relationship between Magic, religion and superstition in different ancient societies and with a sharp updated bibliography which leads us to reflect on the relationship between men and the gods and their different magical religious manifestations.